Isolation of pathogenic strains of methicillin-resistant Staphylococcus aureus from mobile phones in a tertiary institution in Ibadan, Nigeria (2022)
The health implications of mobile phones emission have been a matter of concern to health practitioners for decades but little or no attention has been given to the mobile phones as potential fomites for pathogens. This study isolated and characterised methicillin-resistant Staphylococcus aureus (MRSA) on mobile phones of students in a tertiary institution in Ibadan, Nigeria. One hundred swab samples were obtained from the surfaces of mobile phones of students in a cross-sectional study conducted between July and August, 2019. Presumptive staphylococci were isolated on mannitol salt agar and identities were confirmed by standard biochemical test and Gram-staining. Antimicrobial susceptibility test was done by disc-diffusion method and mecA or mecALGA251, tsst-1, eta and etb genes screened by PCR technique. Among the 200 presumptive S. aureus isolated, 163 (81.5%) were confirmed as S. aureus exhibiting resistance to ofloxacin (1.8%), gentamicin (3.7%), ceftriaxone (29.4%), ceftazidime (57.7%), cefoxitin (61.3%), cefuroxime (64.4%), erythromycin (85.3%), amoxicillin-clavulanic acid (86.5%) and cloxacillin (92%). Proportion of MRSA and methicillin-susceptible S. aureus (MSSA) were 61.3% and 38.7% respectively with significant difference in their level of antibiotic resistance to the cephalosporins (excluding ceftriaxone), penicillins, erythromycin and ofloxacin (p<0.05). All the MRSA strains were multidrug resistant (MDR) harbouring mecA or mecALGA251 (56.3%), tsst-1 (56.3%), etb (31.3%) and eta (12.5%) genes. This study detected a high proportion of methicillin-resistant, virulent S. aureus as fomites on surfaces of mobile phones among students of a tertiary institution. This is of public health concern and thus requires strong public education to avoid imminent spread and outbreaks.